Educational Supervision in Improving the Quality of Education: An Islamic Education Perspective - Cittra Juniarni; Labiba Sonia; Ahmad Maulidin; Eni Uswatun; Nova Asvio (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Educational Supervision in Improving the Quality of Learning: Islamic Education PerspectiveObjective: This study aims to explore the role of supervisors and educational supervision in improving the quality of education from an Islamic education perspective. Method: This research employs a descriptive qualitative approach. Data collection techniques include in-depth interviews, participant observation, document analysis, focus group discussions (FGDs), and literature review. The data were analyzed using content analysis. Results: The findings indicate that educational supervision significantly enhances the professional and technical competencies of teachers, school principals, and other educational staff to foster a higher-quality educational process. In Islamic education, supervision also ensures the integration of Islamic values and objectives into educational practices. Conclusion: Improving the quality of education is a crucial demand that must be fulfilled by every madrasah, especially in responding to the challenges of globalization. Contribution: This study contributes to the academic discourse in the field of Islamic educational supervision by offering a more systematic and innovative approach to enhancing the quality of education based on Islamic values.INDONESIAN: Supervisi pendidikan dalam meningkatkan mutu pendidikan: Perspektif Pendidikan IslamObjektif: Penelitian ini bertujuan untuk mengetahui peran supervisor atau supervisi pendidikan dalam meningkatkan mutu pendidikan dari perspektif pendidikan Islam. Metode: Penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data meliputi wawancara mendalam, observasi partisipan, analisis dokumen, diskusi kelompok terarah (FGD), dan studi literatur. Data dianalisis menggunakan metode analisis isi. Hasil: Hasil penelitian menunjukkan bahwa supervisi pendidikan berperan penting dalam meningkatkan kemampuan profesional dan teknis guru, kepala sekolah, serta tenaga kependidikan lainnya untuk menciptakan proses pendidikan yang lebih bermutu. Dalam pendidikan Islam, supervisi juga memastikan integrasi nilai dan tujuan ajaran Islam dalam praktik pendidikan. Kesimpulan: Peningkatan mutu pendidikan merupakan tuntutan yang harus dipenuhi oleh setiap madrasah, khususnya dalam menghadapi tantangan globalisasi. Kontribusi: Penelitian ini memberikan kontribusi terhadap pengembangan wacana akademik di bidang supervisi pendidikan Islam dengan menawarkan pendekatan yang lebih sistematis dan inovatif untuk meningkatkan kualitas pendidikan berbasis nilai-nilai Islam.